Post thaw evaluation and fertility of bovine semen diluted in Biociphos plus and tris extenders - RAO, N KARUNAKARA; RAO, A SESHAGIRI; NAIDU, K SUBRAMANYAM; NAIDU, K VENUGOPAL; RAO, A MUTHA (The Indian Journal of Animal Reproduction, 2023)
A comparative study on post tliaw semen characteristics and fertility of Murrah and Jersey bull semendiluted with a new yolk free "Biociphos plus" and routinely used yolk containing "Tris" e>..1enders was undertaken.The variation in overall prefreeze motility was found to be significant (P
Keywords: Biociphos plus; tris; semen extenders; post thaw motility of spennatozoa; fertility; bovine semen